FENOMENA PERILAKU POSITIF KASUS GIZI BAIK BALITA PADA KELUARGA MISKIN DI KELURAHAN TAMBELAN SAMPIT PONTIANAK TIMUR - Jahri Jahri (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2021)
Toodler is an age group with rapid body growth. However, toddler is also nutritionally vulnerable group and easily suffer from nutritional disorders. Various studies related to nutrition state that, nutritional status can be caused by medical conditions, socioeconomic status of the family which includes mother's education, mother's work status, family income, household food outcome, and socio-cultural environment. Nevertheless, secondary data in working area of Tambelan Sampit’s Public Health Center, toddlers aged 0-59 months were 85% in good nutrition. This research aimed to explore, analyse, and describe the positive behaviour of housewives in form of parenting’ feeding habits, parenting’s cleaning habits and parenting’s health service with toddler’s good nutrition event from poor family in Tambelan Sampit Urban Village of Pontianak Timur District of Pontianak City. The type of this research was qualitative and the samples were 5 toddlers with good nutrition status from poor family. The samples were taken using purposive sampling, which the housewives were chosen selectively, and they must be the best housewives, would be selected as the research samples. The result showed that positive behaviour of parenting’s feeding habits for toddlers was less eating but it was done regularly, giving additional foods, and giving suplementary vitamines. Parenting’s cleaning habits involved washing hands before feeding the toddler, showering before the feeding, and taking care of the cleanliness of house and environment. While the positive behaviour of parenting’s health service was such as coming to the Integrated Healthcare Center regularly to weigh and to observe the toddler’s health every month, and if the toddler gets sick he or she must be brought to Public Health Center in order to get treatment. This research suggests to improve socialization about nutrition awareness family to increase mother’s knowledge in feeding especially for toddler. It also involves the importance sanitation and hygene, joins the Integrated Healthcare Center regularly, socializes positive behaviours of toddler’s mother from poor family which has been successfully maintained and stayed out of lack nutrition issue on toddlers by health staffs through various activities in Integrated Healthcare Center.